Functionalized coumarin derivatives containing aromatic-imidazole unit as organic luminescent materials. (February 2020) - Wang, Youjia; Li, Yanmei; Yu, Tianzhi; Su, Wenming; Ma, Hailin; Zhao, Yuling; Li, Xinyu; Zhang, Hui
Abstract: Three new coumarin derivatives containing aromatic-imidazole unit (i.e., benzo[ d ]imidazole, phenanthro[9, 10- d ]imidazole and pyreno[4, 5- d ]imidazole), 3-(1-phenyl-1 H -benzo[ d ]imidazole-2-yl)-7-(diethylamino)coumarin (BI–C ), 3-(1-(4-( tert -butyl)phenyl)-1 H -phenanthro[9, 10- d ]imidazole-2-yl)-7-(diethylamino)coumarin (PI–C ) and 3-(9-(4-( tert -butyl)phenyl)-9 H -pyreno[4, 5- d ]imidazole-10-yl)-7-(diethylamino)coumarin (PyI-C ), were successfully prepared for organic light-emitting devices. These compounds show good thermal properties and strong emissions from greenish-blue to green lights owing to the extended π-conjugation of the rigid polyaromatic imidazole skeleton, and have high photoluminescence quantum efficiency of 94%, 97% and 98% in chloroform solutions. Among these compounds, the doped organic light-emitting device fabricated from the compound PI-C exhibited the maximum luminous efficiency of 6.07 cd/A and maximum EQE of 2.78%. Graphical abstract: Image 1 Highlights: Three aromatic-imidazole-based coumarin derivatives were synthesized for OLEDs. They exhibited strong blue-green or green emissions with high photoluminescence quantum yields in dichloromethane solutions. The devices of PI-C exhibited the brightness of 2421 cd/m 2 and luminous efficiencies of 6.07 cd/A, and EQE of 2.78%.